2005
DOI: 10.1073/pnas.0502433102
|View full text |Cite
|
Sign up to set email alerts
|

On class differentials in educational attainment

Abstract: Social class differentials in educational attainment have been extensively studied in numerous countries. In this paper, we begin by examining class differentials in the progression to higher secondary education among 16-year-old children in England and Wales. As has been shown for other countries, the differentials result both from the primary effects of differing levels of academic performance of children of different class background and from the secondary effects of differences in the educational choices t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
203
0
33

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(247 citation statements)
references
References 8 publications
1
203
0
33
Order By: Relevance
“…Sociologists Boudon (1974) and Erikson et al (2010) argue that observed social class schooling differentials result both from the "primary effects" of differing levels of academic performance, i.e. passing or failing, and from the "secondary effects" in the educational choices, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Sociologists Boudon (1974) and Erikson et al (2010) argue that observed social class schooling differentials result both from the "primary effects" of differing levels of academic performance, i.e. passing or failing, and from the "secondary effects" in the educational choices, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Lange Zeit unbefriedigend geklärt war jedoch die quantitative Relation von primären und sekundären Effekten. Methodisch elaborierte Studien aus dem Vereinigten Königreich und Schweden schätzten den Anteil sekundärer Effekte an sozialer Ungleichheit der Bildungsbeteiligung je nach Untersuchungskohorte und Schätzver-fahren auf 20 bis maximal 50 % der Variabilität (Erikson et al 2005;Jackson et al 2007;Erikson & Rudolphi 2009). Für Deutschland liegen drei Untersuchungen vor, die es erlauben, primäre und sekundäre Disparitätseffekte beim Übergang in die weiterführenden Schulen quantitativ zu bestimmen.…”
Section: Soziale Disparitäten Des Kompetenzerwerbs Und Der Bildungsbeunclassified
“…P. 212] for a long time, but more and more empirical studies on inequality in education have been discriminating between primary and secondary effects lately. A statistical method was developed, allowing for the identification of primary and secondary effects of social inequality in educational transitions [Erikson et al, 2005]. A recent comparative study using this method analyzes primary and secondary effects in educational transition to different levels for the US and several European countries [Jackson, 2013].…”
Section: Socioeconomic Aspects Of Inequality In Educational Outcomesmentioning
confidence: 99%